Hubungan antara Status Gizi dengan Gingivitis pada Mahasiswa Program Studi Pendidikan Dokter Gigi Universitas Sam Ratulangi (e-GiGi, 2018)
Abstract: Gingivitis is an inflammation process of gingiva caused by accumulation of biofilm on plaques around the margin of gingiva as well as an inflammation response against bacteria. Nutritional status is affected by macro and micronutrient intake. Poor nutritional status can cause abnormality of function and structure of oral soft tissue resulting in increased plaque forming which leads to the occurence of gingivitis. This study was aimed to obtain the relationship between nutritional status and the occurence of gingivitis. This was an analytical study using a cross-sectional design. Samples were obtained by using total sampling method. There were 77 students as samples. The nutritional status was measured by using body mass index (BMI), and examination of oral cavity was performed to check the occurence of gingivitis. The result showed that 46.8% of students had gingivitis. The nutritional status of the students based on IMT were as follows: 19.5% were categorized as underweight, 65% as normal weight, 9% as overweight, and 6.5% as obese. The bivariate analysis using the Chi-square test showed a P value of 0.000 (